New enzyme-linked immunoassay for the detection of specific antibodies against multiple Leptospira serogroups in bovine sera - Martinez, Mara Leila (2021)
Leptospirosis is a zoonotic disease with worldwide endemicity in Argentina, it is a significant public health problem in low-income populations. Bovine leptospirosis is a serious economic problem for cattle production, causing abortions, reduced milk yield, mortality in calves and decreased daily weight gain. We developed an enzyme-linked immunosorbent assay (ELISA) with sonicated Leptospira interrogans serogroup Icterohaemorrhagiae serovar Copenhageni M 20. We evaluated its performance for the detection of specific antibodies against multiple Leptospira serogroups in bovine. The microscopic agglutination test (MAT) was used as the gold standard. The performance of this ELISA was evaluated with a panel of sera (118 MAT confirmed positive and 97 MAT negative). The overall sensitivity was close to 85.6 % and the specificity was 83.5 %, according to the MAT reference method. Analytical specificity of the IgG-ELISA was evaluated using 50 bovine serum samples from animals showing serum antibodies against other pathogens that cause abortion in bovine, such as Brucella sp., Neospora sp. and Bovine Viral Diarrhea (BVD), and no cross-reaction was observed. This IgG-ELISA can be an alternative to the MAT for diagnosis of leptospiral infection in bovine.